PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) DAN FLASH SALE TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA FAKULTAS EKONOMI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO PADA MARKETPLACE SHOPEE DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING - Holidah, Syarifatul; Wiryaningtyas, Dwi Perwitasari; Praja, Yudha; Ciptasari, Ayu Dita Windra (Fakultas Ekonomi dan Bisnis, 2023)
This study aimed to find out how the effect of Electronic Word Of Mouth (E-WOM) and flash sale on purchase decisions of students at Faculty of Economics, Universitas Abdurachman Saleh Situbondo on Shopee marketplace with trust as an intervening variable. This study used a quantitative approach with a population of 709 people who are students of Faculty of Economics, Universitas Abdurachman Saleh Situbondo, class of 2019 – 2022. The sampling technique in this study used non-probability sampling, namely purposive sampling technique. The sample obtained was 88 respondents. The results of direct effect hypothesis test showed that Electronic Word Of Mouth has a significant positive effect on trust, flash sale has a positive but not significant effect on trust, Electronic Word Of Mouth has a negative but not significant effect on purchase decision, flash sale has a significant positive effect on purchase decision, and trust has a significant positive effect on purchasing decisions. The results of indirect effect hypothesis test indicated that Electronic Word of Mouth has a positive but not significant effect on purchase decisions through trust as an intervening variable, flash sale has a positive but not significant effect on purchase decisions through trust as an intervening variable.